2012
DOI: 10.1371/journal.pone.0030907
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Candidate Oncogenes in Chromosome Region 17p11.2-p12 in Human Osteosarcoma

Abstract: Osteosarcoma is the most common primary malignancy of bone. The tumours are characterized by high genomic instability, including the occurrence of multiple regions of amplifications and deletions. Chromosome region 17p11.2–p12 is amplified in about 25% of cases. In previous studies, COPS3 and PMP22 have been identified as candidate oncogenes in this region. Considering the complexity and variation of the amplification profiles for this segment, the involvement of additional causative oncogenes is to be expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 54 publications
(66 reference statements)
2
36
1
Order By: Relevance
“…28 And it was reported that COPS3 is a candidate oncogene of importance in OS tumorigenesis. 31 Functional studies will be needed to test for their oncogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…28 And it was reported that COPS3 is a candidate oncogene of importance in OS tumorigenesis. 31 Functional studies will be needed to test for their oncogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Among all the genes detected underlying QTL on chromosome 10, several genes have previously shown to play important functions in bone growth and remodeling (Table 2). Cops3 is an oncogene residing in the human chromosomal region 17p11.2-p12 - the copy number and expression level of Cops3 was significantly associated with the development of osteosarcoma, the most common primary malignancy of bone [29,30]. Drg2 , a GTP binding protein, overexpression of which in transgenic mice leads to increased number and activity of osteoclasts and bone loss [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of Rai leads to craniofacial and skeletal anomalies (short extremities) in Smith-Magenis syndrome [32]. Both the copy number and expression level of Rasd1 were significantly associated with the development of osteosarcoma [29]. In addition, using an integrative genetics approach, Rasd1 was identified as a strong candidate gene for a BMD QTL in mice [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification of the chromosome 17p11.2 region and PMP22 expression have been associated with human osteosarcoma and glioblastoma in tissue and cell lines. 3136 Moreover, in vitro and in vivo data suggest PMP22 may play a role in the neoplastic transformation process of the normal pancreas to premalignant lesions to pancreatic cancer. 37 This varied expression in different tumor types suggests that the role of PMP22 in growth arrest and differentiation may be cell and tissue specific.…”
Section: Pmp22mentioning
confidence: 99%